2016
DOI: 10.1210/jc.2016-1645
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Treatment and Sexual Function in Older Men With Low Testosterone Levels

Abstract: In older men with low libido and low T levels, improvements in sexual desire and activity in response to T treatment were related to the magnitude of increases in T and estradiol levels, but there was no clear evidence of a threshold effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 43 publications
2
83
1
2
Order By: Relevance
“…260 An RCT in 470 men aged >65 years with testosterone levels <275 ng/dL found that testosterone gel led to improvements in sexual function, desire, and activity. 261,262 Other studies have shown that the addition of testosterone to PDE5i therapy in men with low serum testosterone levels helps improve ED. 263268 Testosterone therapy should not be used if contraindicated by the primary oncologic diagnosis (eg, prostate cancer on active surveillance, prostate cancer on ADT).…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…260 An RCT in 470 men aged >65 years with testosterone levels <275 ng/dL found that testosterone gel led to improvements in sexual function, desire, and activity. 261,262 Other studies have shown that the addition of testosterone to PDE5i therapy in men with low serum testosterone levels helps improve ED. 263268 Testosterone therapy should not be used if contraindicated by the primary oncologic diagnosis (eg, prostate cancer on active surveillance, prostate cancer on ADT).…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…Studies have observed that men who have been placed on androgen deprivation therapy (ADT) for prostate cancer have a dramatic reduction in erectile function with a decrease in testosterone levels [1618]. Finally, numerous randomized controlled trials (RCTs) have demonstrated that erectile function improves when testosterone is given to men with low testosterone levels [1924]. …”
Section: Testosterone Therapy Improves Symptoms Of Mild Erectile Dysfmentioning
confidence: 99%
“…The recently published Testosterone Trials – a set of RCTs of 790 men with late onset hypogonadism randomly assigned to either testosterone gel or placebo – demonstrated that after 1 year of treatment that men who used testosterone gel had an IIEF-ED score 2.64 points [95% Confidence Interval (CI): 1.06 – 4.02] greater than men who had been assigned to the placebo arm [24]. It is important to note that men enrolled in this study on average had moderate ED, and so this improvement in erectile function was not considered clinically significant.…”
Section: Testosterone Therapy Improves Symptoms Of Mild Erectile Dysfmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of validity of the study design, randomized controlled trials (RCT’s) have the highest validity, followed by prospective studies. However, most randomized trials of TTh are not powered to investigate their effect on CVD outcomes (28). …”
Section: High Serum Total- Free- and Bioavailable-testosterone And Cmentioning
confidence: 99%